Odpowiedź :
Odpowiedź:
Odpowiedz w załączniku
Szczegółowe wyjaśnienie:
![Zobacz obrazek Tomaszjedrzychp2z1e4](https://pl-static.z-dn.net/files/d85/21484a377ed7f5715b8935a7117ef40b.jpg)
Odpowiedź:
a) 6(x-4)-2 = 6x - 24 - 2 = 6x - 22
b) 2(x+1) - 3(x-1) = 2x + 1 - 3x - 3 = -1x - 2
c) -3(y-2) + 4(y+2) = (-3y) + 6 + 4y + 8 = y + 14
d) 5(x - y - 1) - 4(x + 2) = 5x - 5y - 5 - 4x - 8 = -9x - 5y - 13
e) 2(3a + b)2(a - b) = 6a + 2b x 2a -2b = 12a2 - 4b2
f) 1/2(4x - 4) - 2x = 2x - 2 - 2x = -2
g) x(x - 1)-3(x2 - x) = x2 - x - 3x2 + 3x = -2x2 + 2x
h) 5a(a - 3)-3a(a -5) = 5a2 - 15a - 3a2 + 15a = 2a2
Szczegółowe wyjaśnienie: